Potensi Formulasi Self Microemulsifying Drug Delivery System (SMEDDS) Ekstrak Biji Kedelai (Glycine soja) Terhadap Penurunan Kolesterol pada Penyakit Jantung Koroner - I Nengah Raka Swastika; Ni Ketut Ristiani; Adrian Wiryanata Gorintha; Agung Wiwiek Indrayani (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: Coronary heart diseases (CHD) is a disorder that caused by blockage of coronary arteries due to the process of atherosclerosis which disrupts the blood supply to the heart muscle. According to Sample Registration System (SRS) Indonesia in 2014, CHD is a second highest cause of death after stroke that is 12,9% of all cause of death in Indonesia. Therefore, this study aims to examining the effect of soybean extract encapsulated with Self Microemulsifying Drug Delivery System (SMEDDS) on LDL levels in coronary heart model rats. Based on various study, isoflavone aglycone genistein is the main flavonoid in soybean seed that has potential as an antioxidant. To increase bioavailability of aglycone isoflavones, a SMEDDS is needed. In this regard, the purpose of this reseach is to examine the potential of soybean seed (Glycine soja) extract to reduced cholesterol in CHD.Methods: The method used is a literature review with literature sources in the form of relevant articles from the search engines, namely Google Scholar, Pubmed, ScienceDirect, and Research Gate. Inclusion criteria included journals containing the keywords “soybean (Glycine soja)”, “Coronary Heart Disease”, “SMEDDS”, and “genistein isoflavone aglycone”.Result: Isoflavone aglycone as an potential antioxidant that is able to bind free radicals and and also lowering LDL, Triglycerides, and glucose levels in hyperglycemic states and increasing HDL.Conclusion : Soybean seed extract with SMEDDS encapsulation have a potential to decrease LDL level in coronary heart disease.